Study the association between myeloperoxidase gene single-nucleotide polymorphism G463A (rs2333227) and coronary artery disease in Iraqi patients - Wisal Abdulrhman Salem; Dawood Salman Ali; Hamid Jaddoa Abbas (Universitas Nahdlatul Ulama Surabaya, 2026)
Acute coronary syndrome (ACS) is a major cause of morbidity and death globally, which is caused by the multifaceted interaction between oxidative stress and inflammatory processes. The enzyme myeloperoxidase (MPO) is secreted by activated leukocytes and is a determinant of vascular dysfunction and unstable plaque. The genetic variation within the MPO gene, especially G463A (rs2333227), may increase enzyme expression and contribute to disease occurrence. The aim of the study was to examine the relationship between the MPO G463A polymorphism, circulating MPO levels, and the risk of ACS. The case-control study included 129 patients with ACS and 66 apparently healthy controls. Immunoassay techniques were used to measure serum MPO and high-sensitivity troponin I levels, and PCR-based methods were used to assess the MPO G463A polymorphism. The MPO level in serum was significantly higher in ACS patients than in controls (p < 0.001). The ROC analysis revealed an average diagnostic ability for MPO (AUC = 0.686, sensitivity for70.7%). There was a significant association between the MPO G463A polymorphism and ACS susceptibility (p > 0.05). Nonetheless, some genotypes were correlated with changes in MPO levels, and they may contribute to the severity of the diseases. An elevated serum MPO level is strongly correlated with ACS and can serve as a useful biomarker for its detection. Conversely, the MPO G463A polymorphism does not appear to have a significant impact on disease susceptibility but may affect individual differences in the inflammatory response.